Pedagogical and Psychological Aspects of Professional Sustainability of Future Teachers - Norkuzieva Manzura Abdurahmonovna (Research Parks Publishing LLC, 2021)
This article focuses on the issue of pedagogical-psychological approach in the professional adaptation of future teachers and ensuring its sustainability.